al-Ṭabʻah al-Ūlá min al-Manāhij al-ʻUmānīyah (1978-1984 M.): Dirāsah Taḥlīlīyah - Barāshdī, Mūsá ibn Sālim ibn Ḥamad; Raḥbī, Khālid ibn Muḥammad ibn ʻAdī (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
School curricula are among the important documents in the history of states and peoples, reflecting their hopes, ambitions, aims and the questions that occupy them across the different periods. In Oman, after the modern renaissance under Sultan Qaboos bin Said, curricula were brought in from certain Arab countries pending sound planning for their Omanisation, this being an essential requirement for planting the values of citizenship in students. That stage began with the continued application of those imported curricula, foremost the Qatari curriculum, before the first launch of Omani curricula in the 1978/1979 academic year. The paper examines the history of the Omani curricula in terms of the date of their printing and the drawing of their policies beforehand, in addition to analysing the contents of that first edition.
MHF-PRINT2018-031
Keywords: Omani curricula; Education history; Textbook printing; Citizenship values; Curriculum analysis; Oman